Figure 2 from Exploiting Natural Killer Cell Engagers to Control Pediatric B-cell Precursor Acute Lymphoblastic Leukemia - Natalia Colomar-Carando (14611340) (2025)
NKCEs enhance NK-cell activity against MHH-CALL-4 cell line. CD107a expression and IFNγ production by resting NK cells from healthy donors (n = 3–6) cocultured for 6 hours with MHH-CALL-4 cells in the absence or presence of CD19-NKCEs, CD20-NKCEs, or the control molecules (IC-NKp46-NKCE, IC-NKp30-NKCE) at 10−2 μg/mL and 100 μg/mL. A, Flow cytometry of a representative experiment is shown. Numbers indicate the percentage of cells in each quadrant. CD107a expression (B) and IFNγ production (C) were performed in 3–6 independent experiments. Bars show mean ± SEM. Statistical significance: *, P ≤ 0.05; **, P ≤ 0.01; ***, P ≤ 0.001. Two-way ANOVA followed by Tukey test was used to calculate statistical differences among the indicated NKCEs within each concentration. Mann–Whitney test was used to compare each NKCE at the two indicated concentrations.